Migration Policy is Heading Down a Beaten Track. Comment on the Judgment of the European Court of Human Rights in the R.R. and others v. Hungary Case of 5 July 2021 - Kun-Buczko, Magdalena (Polish Review of International and European Law, 2023)
In July 2021, the Grand Chamber of the European Court of Human Rights (ECHR) delivered a judgment in the R.R. v. Hungary case which perpetuates previous case law on obligations in providing migrants with international protection. The judgment is also of critical importance in view of the Common European Asylum System. The ECHR has confirmed that Hungary had failed to full its obligations in providing migrants with international protection especially when it comes to the length of time applicants were deprived of their liberty and the extent of the protection afforded to the pregnant applicant and her minors.